Relação entre prioridades competitivas e estrutura organizacional: estudo multicasos em empresas do setor de autopeças de Sorocaba - Oliveira, Lucas Gabriel Brito de (2017)
The production strategy has been considered important to obtain advantages over competitors. Its content is made up of competitive priorities and decision categories (or areas) that should develop such priorities. Among these categories, there is the organizational structure that should have characteristics that foster the priorities adopted by the organization. In this context, the present work seeks to identify which is the competitive priority of the companies in the auto parts sector of the city of Sorocaba and how the organizational structure can favor its development. Through a qualitative study, using the methodology of study of multicases, the organizational structures that favor the development of one or more competitive priorities were identified and compared. In the four companies studied it was observed that the competitive priority is quality. In these companies, the characteristics of the organizational structure that favor this competitive priority are the high degree of formalization of the activities, the decentralization of the decisions, training, the awareness of the leaders on the importance of quality, and the incentive to the formal and informal communication in the group work and meetings.